Diseño de un plan de mejoramiento para el área administrativa, financiera y de producción de la industria textil “rima” productora y distribuidora de uniformes para escuelas y colegios ubicada en la provincia Pichincha en el Distrito Metropolitano de Quito. - Ríos Mantilla, Carol Cristina (2014)
The current proposal is an improvement plan for administration, financial area and production at the Textile Enterprise RIMA that is a producer and distributor of uniforms, located in Pichincha Province in the Metropolitan District of Quito from 2012 to 2013. The purpose is an application of an improvement plan, using the process design that encompasses administrative, financial area and production in order for RIMA Company to increase their competitiveness, secure profit rates, to improve the quality of their products and to satisfy their customer. This analyzing the Internal and the External Factor (macroenvironment, microenvironment) of RIMA determined the present situation of the Company and the design of control system and continuous evaluation of production, marketing and internal management incorporating innovation technology in all areas of the company is proposed, so the wasted of raw materials, energy and supplies are prevented, at the same time optimizing active time of labor working in the plant,